2019
DOI: 10.1007/s00391-019-01644-x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot observational study to analyze (in)activity and reasons for sedentary behavior of cognitively impaired geriatric acute inpatients

Abstract: A pilot observational study to analyze (in)activity and reasons for sedentary behavior of cognitively impaired geriatric acute inpatients Observation To gain context information patients were directlyobserved bythe method ofbehavioral mapping (NB). Each observation took place only on the following day of the patient's individual assessment. Obser-S274 Zeitschrift für Gerontologie und Geriatrie • Suppl 4 • 2019

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
(30 reference statements)
0
14
0
1
Order By: Relevance
“…Participants Most studies concerned general acute medical patients ( n = 11, mean sample size 114, range 16–287). Five studies were exclusively concerned with patients with specific conditions; two each reported physical activity levels of patients with acute exacerbations of chronic obstructive pulmonary disease (mean sample size 13.5, range 10–17) [ 30 , 32 ], and heart failure (mean sample size 36, range 27–45) [ 33 , 35 ] and whilst one reported on patients with mixed medical conditions plus mild-moderate cognitive impairment (sample size 20) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants Most studies concerned general acute medical patients ( n = 11, mean sample size 114, range 16–287). Five studies were exclusively concerned with patients with specific conditions; two each reported physical activity levels of patients with acute exacerbations of chronic obstructive pulmonary disease (mean sample size 13.5, range 10–17) [ 30 , 32 ], and heart failure (mean sample size 36, range 27–45) [ 33 , 35 ] and whilst one reported on patients with mixed medical conditions plus mild-moderate cognitive impairment (sample size 20) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 ). The studies that performed better in the analysis [ 34 , 36 38 ] gave greater consideration to reporting information on non-responders (patients that were eligible for inclusion but declined to participate).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is necessary to point out that most studies in the area of old age have focused on cognitive impairment [42,43], strength and agility [44], or on the pathological perspective of old age (e.g., Alzheimer's) [45]. Hence, there are few scientific studies at present that have focused on the positive promotion of health as well as other profiles without pathologies.…”
Section: Discussionmentioning
confidence: 99%